2022
DOI: 10.3390/medicina58101447
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of Robotic Rehabilitation Assisted Devices Following Spinal Cord Injury and the Prevention of Secondary Associated Complications

Abstract: Spinal cord injuries (SCIs) have major consequences on the patient’s health and life. Voluntary muscle paralysis caused by spinal cord damage affects the patient’s independence. Following SCI, an irreversible motor and sensory deficit occurs (spasticity, muscle paralysis, atrophy, pain, gait disorders, pain). This pathology has implications on the whole organism: on the osteoarticular, muscular, cardiovascular, respiratory, gastrointestinal, genito-urinary, skin, metabolic disorders, and neuro-psychic systems.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 90 publications
1
7
0
1
Order By: Relevance
“…The current study reveals a lack of statistically significant correlation between BMI and sex, aligning with numerous similar studies conducted by peers (15,16). In certain studies investigating muscle or bone mass loss, a parallel relationship between age and BMI can be observed (17,18). In this particular study, the correlation between age and BMI was not found to be statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…The current study reveals a lack of statistically significant correlation between BMI and sex, aligning with numerous similar studies conducted by peers (15,16). In certain studies investigating muscle or bone mass loss, a parallel relationship between age and BMI can be observed (17,18). In this particular study, the correlation between age and BMI was not found to be statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…Current treatment for PD is mainly symptomatic, including levodopa, dopamine agonists, catechol-O-methyltransferase inhibitors and monoamine oxidase B inhibitors. Nevertheless, these medicines are focused on PD manifestations rather than limiting disease progression [ 50 ]. Likewise, other groups of drugs, such as the AchEIs, memantine and atypical antipsychotics, are focused on treating non-motor symptoms, such as apathy, depression and autonomic dysfunction.…”
Section: Indp In Chronic Neurodegenerative Diseasesmentioning
confidence: 99%
“…The impact of robotics resonates beyond the confines of the operating room, extending to the rehabilitation phase. Robotics-assisted rehabilitation devices, including exoskeletons and motion-capture systems, are revolutionizing how patients regain mobility and strength after orthopedic procedures [ 6 ]. These devices provide targeted exercises, monitor progress, and adjust the rehabilitation regimen based on real-time data, thus ensuring optimal recovery trajectories.…”
Section: Editorialmentioning
confidence: 99%